A house like a Lotus - L'Engle, Madeleine (Laurel-leaf books, 1985)
While working at a conference in Cyprus, sixteen-year-old Polly tries to come to terms with the emotionally tumultuous events preceding her arrival on the island and her relationships with old and new friends.